2011
DOI: 10.1002/jbm.a.33224
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of the migration of endothelial cells and fibroblasts on polyurethane nanocomposites by the activation of integrin‐focal adhesion kinase signaling

Abstract: Model surfaces of polyurethane-gold nanocomposites (PU-Au) were used to examine cell behavior on nanophase-segregated materials. Previously we showed that endothelial cell (EC) migration on these materials was modulated by the PI3K/Akt/eNOS pathway. The present study, investigated the expressions of alpha5/beta3 (α5β3) integrin, focal adhesion kinase (FAK), and other downstream signal molecules such as the Rho family and matrix metalloproteinases 2 (MMP-2) induced by the materials in two different cells, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…the amount of AuNPs required to change the microstructure may be low. In this situation, a higher concentration of AuNPs often leads to overloading and aggregation of nanoparticles, which adversely interferes with the microstructure and biological performances of the polymer [33], [34], [36]. In this study, the characteristic dimension of collagen in the presence of 43.5 ppm AuNPs was consistent with the favorable dimension in literature (∼100 nm), while the pure collagen revealed the less preferable dimension (∼15 nm).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…the amount of AuNPs required to change the microstructure may be low. In this situation, a higher concentration of AuNPs often leads to overloading and aggregation of nanoparticles, which adversely interferes with the microstructure and biological performances of the polymer [33], [34], [36]. In this study, the characteristic dimension of collagen in the presence of 43.5 ppm AuNPs was consistent with the favorable dimension in literature (∼100 nm), while the pure collagen revealed the less preferable dimension (∼15 nm).…”
Section: Discussionsupporting
confidence: 86%
“…Previously we showed that addition of AuNPs into polyurethane, a non-biodegradble polmer, could trigger the αvβ3 integrin/FAK and PI3K/Akt/eNOS signaling pathways and modulate the migration of endothelial cells [33], [34]. In this work, the better stem cell functions on Col-Au nanocomposites were also associated with αvβ3/CXCR4 integrin/FAK/MMP-2 signaling pathway and regulation of Akt/eNOS protein expression.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Endothelial progenitor cells, smooth muscle cells and microporous poly glycolic acid -poly -L -lactic acid) scaffolds in vitro bath, bracket produced capillary like structures. Hung HS [4] and so on, which will be seeded with endothelial progenitor cells, the thin film coated with gelatin coated with a thin layer of polyurethane patch, which is placed in the dog's bilateral internal carotid artery, 1 months and 3 months after implantation, the observation and study of the internal carotid artery intima covered circular stone like monolayer cells, 300 months of new arterial wall thickness of 3 microns, a small amount of smooth muscle cell proliferation, local no thrombosis. In addition to endothelial progenitor cells, vascular endothelial cells, smooth muscle cells, stromal cells can be used as seed cells seeded on the scaffold, which carries the lesion to the lesion site, and can achieve local localization, migration, differentiation and functional expression of cells.…”
Section: Intravascular Stentmentioning
confidence: 99%